FORMATION OF PEDAGOGUE'S STRESS RESISTANCE - Alexander Volkov; Olga Chursinova; Gemma Gasparyan (Вестник Северо-Кавказского федерального университета)
The article describes the main approaches to the concept of «stress». Stress is the key to the preservation, development and strengthening of mental and physical health of a person, so the teacher must master the skills of controlling your emotions in order to maintain health under stressful conditions. The authors have developed and described a model of formation ofstress a teacher, includes four major blocks: target, substantial, procedural, effective.